The Implementation of Supreme Court Regulation Number 2 of 2012 concerning Limitation Adjustment of Mild Criminal Offenses and Amount of Fines in the Criminal Code Towards Handling of Minor Crime Cases - Abbas Sofwan Matlail Fajar; Mara Sutan Rambe (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2019)
Abstract:The case of theft with a small value of goods which is now being tried in court is quite under public’s spotlight, public are generally considering that it is very unfair if the cases are threatened with a penalty of 5 (five) years as determined in article 362 of the Criminal Code. Since the punishment is not comparable to the value of the stolen goods, these cases have also encumbered the court, both in terms of the budget and public perceptions of the court. After analyzing the problem, the authors concluded that the application of PERMA Number 2 of 2012 as for Adjustment of Light Crime Limits and the Amount of Mulcts in the Criminal Code has not been used as a Court or Judge as a material consideration or a reference to decide criminal acts whose goods value is below IDR 2,500,000.00 (two million five hundred thousand rupiah).Keywords: Supreme Court Regulations, Mild Crimes, Fines Abstrak:Perkara pencurian dengan nilai barang yang kecil yang kini diadili di pengadilan cukup mendapat sorotan masyarakat, masyarakat umumnya menilai bahwa sangatlah tidak adil jika perkara-perkara tersebut diancam dengan ancaman hukuman 5 (lima) tahun sebagaimana diatur dalam pasal 362 KUHP. Oleh karena tidak sebanding dengan nilai barang yang dicurinya, perkara-perkara tersebut juga telah membebani pengadilan, baik dari segi anggaran maupun dari segi persepsi publik terhadap pengadilan. Setelah melakukan analisa terhadap permasalahan, penulis berkesimpulan bahwa penerapan PERMA Nomor 2 Tahun 2012 Tentang Penyesuaian Batasan Tindak Pidana Ringan dan Jumlah Denda dalam KUHP belum dijadikan Pengadilan atau Hakim sebagai bahan pertimbangan atau pun acuan untuk memutus tindak pidana yang nilai barangnya di bawah Rp. 2.500.000,00 (dua juta lima ratus ribu rupiah).Kata Kunci: Peraturan Mahkamah Agung, Tindak Pidana Ringan, DendaАннотация:Дело о краже с небольшой стоимостью товаров, которое сейчас рассматривается в суде, находится в центре внимания общественности, общественность, как правило, считает, что очень несправедливо, если этим случаям грозит штраф в 5 (пять) лет, как определено в статье. 362 УК РФ. Поскольку наказание несопоставимо со стоимостью похищенных товаров, эти дела также обременяют суд, как с точки зрения бюджета, так и общественного восприятия суда. Проанализировав проблему, авторы пришли к выводу, что применение PERMA № 2 от 2012 года в отношении корректировки пределов легкой преступности и количества элементов в Уголовном кодексе не использовалось в качестве суда или судьи в качестве материала для рассмотрения или ссылки на принимать решения о преступных деяниях, стоимость товаров которых ниже 2 500 000,00 (два миллиона пятьсот тысяч) рупий.Ключевые слова: постановление Верховного суда, легкие преступления, штрафы